2016
DOI: 10.1515/mgr-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Teenage overweight and obesity: A pilot study of obesogenic and obesoprotective environments in the Czech Republic

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Considering that the individual genetic and lifestyle factors attribute in part to the global increase in the prevalence of obesity and overweight in recent years, the multifactorial nature of overweight has attracted much attention to researching on modifiable environmental characteristics [ 10 , 11 ]. Living environmental factors influence students’ life behaviours and affect their energy intake and consumption, leading to different health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the individual genetic and lifestyle factors attribute in part to the global increase in the prevalence of obesity and overweight in recent years, the multifactorial nature of overweight has attracted much attention to researching on modifiable environmental characteristics [ 10 , 11 ]. Living environmental factors influence students’ life behaviours and affect their energy intake and consumption, leading to different health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…modi able environmental characteristics. 8,9 Living environmental factors in uence students' life behaviours and affect their energy intake and consumption, leading to different health outcomes. It is reported that an increased number of tness facilities were associated with a reduction in teenagers' body weight, which provided more opportunities to access to recreational facilities to increase their daily exercise.…”
Section: Introductionmentioning
confidence: 99%
“…However, if consumed in large quantity, dietary fat may lead to different health complications such as obesity, the metabolic syndrome, cancer, type 2 diabetes mellitus (T2DM) ( 2 ) and Alzheimer’s disease ( 3 , 4 ) . As far as the incidence of obesity is concerned, the Czech Republic ranks at the fourth place in Europe ( 5 ) .…”
mentioning
confidence: 99%